Clinical Performance of Direct Anterior Composite Restorations in Mixed Dentition: A randomized cross-sectional study - Can Özükoç (Innovative Journal of Medical and Health Sciences, 2020)
Aim: Direct anterior composite restoration is the first preferred method for children in the mixed dentition stage to replace dental tissue lost to caries, trauma or similar reasons. This study aimed to evaluate the effect of cavity type and treating institution on clinical longevity of direct anterior composite restorations in children in the mixed dentition stage. Material method: The data obtained from 114 direct anterior composite restorations performed in different institutions using the Modified USPHS criteria were evaluated according to cavity types and types of institutions where restorations were performed. Results: It was found that the mean values of retention, marginal adaptation and postoperative sensitivity were higher in class IV restorations, the highest values were obtained from the restorations performed at the Public Oral Health Center, and there was a statistically significant difference. (p<0.05) Conclusion: Although it has been shown that the clinical longevity of class IV composite restorations is shorter than other types of restoration in children in the mixed dentition stage, restorations performed at the University Dental Clinic have been found to be more successful. Key words: Anterior restoration, Composite restoration, Direct composites, Pediatric dentistry, USPHS